PENGARUH KEJELASAN SASARAN ANGGARAN, EVALUASI ANGGARAN, DAN KUALITAS SUMBER DAYA MANUSIA TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI ( Studi Pada OPD Kabupaten Lima Puluh Kota ) - Eugina, Utami Fiska; Edfan Darlis, Edfan Darlis; Yuneita, Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to examine the Effect of Clarity of Budget Objectives, Budget Evaluation, and Quality of Human Resources on Performance Accountability of Government Agencies with Organizational Commitment as a Moderation Variable. The population in this study were all OPDs in the Fifty Cities District. In this study, the sample used is 84 respondents who were selected using purposive sampling method. This study uses primary data by distributing questionnaires. The analytical method used in this research is multiple linear regression analysis and moderated regression analysis. The analytical tool used in this research is the Statistical Product and Service Solution (SPSS) version 25.0. The results of this study indicate that: (1) clarity of budget targets affects the performance accountability of government agencies, (2) budget evaluation affects the performance accountability of government agencies, (3) the quality of human resources affects the performance accountability of government agencies (4) organizational commitment can moderate the relationship between budget clarity on the performance accountability of government agencies (5) organizational commitment can moderate the relationship between budget evaluation and accountability for the performance of government agencies (6) organizational commitment can moderate the relationship between the quality of human resources and the performance accountability of government agencies.Keywords : Clarity of Budget Targets, Budget Evaluation, Quality of Human Resources, Organizational Commitment, Accountability for Performance of Government Agencies (AKIP)